ANALISIS STRATEGI PENINGKATAN PENDAPATAN ASLI DAERAH (PAD) DI KABUPATEN LAMPUNG BARAT - -, Hasanusi (Jurnal Manajemen Magister Darmajaya, 2015)
The reception area is a source of income that must be managed properly which is useful for supporting development in the area. The strategy that has been done by PPKAD agency to increase local generated revenue can be seen in the vision and mission agency PPKAD in Strategic Management aspects. Since the last five years, the contribution of local revenue (PAD) to the local government budget (APBD) on average each year is still below 4%, and the contribution of local taxes to PAD average of 17.5% annually. This is due not optimal the efforts intensification and extension undertaken West Lampung district government in increasing local tax revenue. This research will formulate a strategy to increase local taxes in West Lampung. The method used in this research is descriptive, with a qualitative approach. Descriptive method is to make the description / picture / painting in a systematic, factual and accurate information on the facts, as well as the properties and relationships between phenomena. The direct approach is used as a basis for the formulation of a problem. While the data analysis using the SWOT analysis and Litmus test. Strategic factors that can increase local tax revenues, namely: data collection on taxpayers, cooperation with the private sector / NGOs in the management and collection of local taxes, revamping of the management of local taxes, give the sanctions for violations of local taxes, expanding tax-base of the area taxes, re-identification of the mission and mandate of the organization, Applying computerized reception area at the Department PPKAD.Keywords: pajak daerah, kontribusi, PAD, Managemen Strategi, Intensifikasi dan ekstensifikasi